The role of water and structure on the generation of reactive oxygen species in peptide/hypericin complexes‡. (20th May 2014) - Souza, Márcia I.; Silva, Emerson R.; Jaques, Ygor M.; Ferreira, Fabio F.; Fileti, Eudes E.; Alves, Wendel A.; Morelli, Giancarlo; Toniolo, Claudio; Venanzi, Mariano
<x xml:space="preserve">Abstract</x> Hybrid associates formed between peptide assemblies and fluorophores are attractive mainly because of their unique properties for biomedical applications. Recently, we demonstrated that the production of reactive oxygen species (ROS) by hypericin and their stability in excited states are enhanced upon conjugation with l, l‐diphenylalanine microtubes (FF‐MNTs). Although the detailed mechanisms responsible for improving the photophysical properties of ROS remain unclear, tentative hypotheses have suggested that the driving force is the growth of overall dipolar moments ascribed either to coupling between aligned H2O dipoles within the ordered structures or to the organization of hypericin molecules on peptide interfaces. To provide new insights on ROS activity in hypericin/FF‐MNTs hybrids and further explore the role of water in this respect, we present results obtained from investigations on the behavior of these complexes organized into different crystalline arrangements. Specifically, we monitored and compared the photophysical performance of hypericin bound to FF‐MNTs with peptides organized in both hexagonal (water‐rich) and orthorhombic (water‐free) symmetries. From a theoretical perspective, we present the results of new molecular dynamics simulations that highlight the distinct hypericin/peptide interaction at the interface of FF‐MNTs for the different symmetries. As a conclusion, we propose that although water enhances photophysical properties, the organization induced by peptide structures and the availability of a hydrophobic environment surrounding the hypericin/peptide interface are paramount to optimizing ROS generation. The findings presented here provide useful basic research insights for designing peptide/fluorophore complexes with outstanding technological potential. Copyright © 2014 European Peptide Society and John Wiley & Sons, Ltd.